2013
DOI: 10.1016/j.jlumin.2012.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and spectroscopic–electrochemical properties of novel ratiometric Hg (II) chemosensor containing Bodipy and the N-phenylaza-15-crown-5 moiety

Abstract: The aryl-amine containing azacrown ether ring and alkyl-chloro boradiazaindacene (Bodipy) were synthesized by Schiff base condensation. The absorption and emission of a novel Schiff base derivative (based on azacrown-Bodipy ) were performed in presence of different cations such as Zn2+, Ga3+, Pb2+, Hg2+, NH4+ Ca2+, Cu2+, Na+, Ni2+, Cd2+ and Cr3+. The complexation property of the Schiff base was studied in dimethylformamide (DMF) by interacting azacrown-ether group and transition metal nitrates-ammonium chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…1 H-NMR [CDCl3, 400 MHz]: 8.65 (3H, bs, NH), 8.39 (3H, s, ArH), 7.48-7.15 (12H, m, ArH), 4.48 (CH2, s, 6H,), 2.48 (CH3, s, 18H,), 2.15 (CH2, q, 12H), 1.60 (CH3, s, 18H), 1.12 (CH3, t, 12H). 13…”
Section: The Synthesis Of T-bodipyunclassified
See 1 more Smart Citation
“…1 H-NMR [CDCl3, 400 MHz]: 8.65 (3H, bs, NH), 8.39 (3H, s, ArH), 7.48-7.15 (12H, m, ArH), 4.48 (CH2, s, 6H,), 2.48 (CH3, s, 18H,), 2.15 (CH2, q, 12H), 1.60 (CH3, s, 18H), 1.12 (CH3, t, 12H). 13…”
Section: The Synthesis Of T-bodipyunclassified
“…The use of Bodipy compounds has been reported in the field of fluorescent probes for detection of various cations [7][8][9]. Reportedly, Bodipy is of noteworthy synthetic versatility, high solubility, stability and optical properties Bodipy can also be used as a ligand for metals which require different coordination spheres [10][11][12][13]. Although these Bodipy fluorescent compounds exhibited a good selectivity&sensitivity for the recognition of metal cations, the reported chemosensors were not soluble in pure water [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are commonly considered functional cages because of their ability and selectivity to heavy or alkali metal sensors by using light. Furthermore, dibenzo 18 crown-6 ether derivatives proposed as effective highly selective chemosensor for Hg 2+ and Al 3+ [33][34][35] .…”
Section: Absorption Spectramentioning
confidence: 99%
“…Jouanneau et al improved heavy metal detection using different strains of E. coli as bioluminescence bacteria [29,30]. Kursunlu et al and Sulak et al designed and prepared fluorescent alkyl-chloride boradiazaindacene (Bodipy) based sensors [31][32][33]. ey showed that Calix [4]-B (obtained by click reaction [31] and a fluorescent Bodipy with alkylchloride terminal) [32], aryl-amine (containing azacrown ether ring and Bodipy) and on/off rhodamine-Bodipy (RB) [33] are appropriate sensors which could be used for high sensitivity detection of mercury ion.…”
Section: Introductionmentioning
confidence: 99%